The emergence of nitrification during DOM processing by marine microbial assemblages - Kevin J. Flynn; Darren R. Clark; Karen Tait; Susan A. Kimmance; Elaine S. Fileman; Luca Polimene (PLoS ONE, 2025)
Dissolved organic matter (DOM) production, its degradation, and nitrification, are crucial interconnected processes in the ocean. Nitrate produced by nitrification supports oceanic primary production. Primary production is the main source of DOM which, when remineralised by heterotrophic bacteria, liberates ammonium, the substrate supporting activities of nitrifying bacteria and archaea. However, the mechanisms underpinning the interplay between these processes, their succession and feedback, remain poorly understood. To elucidate these dynamics, we conducted two distinct DOM degradation experiments where natural marine microbial communities were exposed to microalgal-derived DOM. After 150 d of DOM degradation, we observed a strong consumption of ammonium and an increase in nitrate concomitantly with increased presence of nitrifying prokaryotes. The time course of this event suggests that, when ammonium is not limiting, nitrification in the oceans is regulated by competition between nitrifiers and heterotrophic bacteria with growth of the latter being more efficient when sufficient labile DOM is available. However, carbon limitation due to progressive consumption of labile DOM and enrichment of recalcitrant compounds transfers competitive advantage to nitrifiers, in this way contributing to the emergence of nitrification. This hypothesis is supported by numerical simulations showing an increasing dominance of nitrifying groups concomitantly with increasing DOM recalcitrance.